2006
DOI: 10.1002/sia.2274
|View full text |Cite
|
Sign up to set email alerts
|

Simple surface treatments to modify protein adsorption and cell attachment properties within a poly(dimethylsiloxane) micro‐bioreactor

Abstract: Poly(dimethylsiloxane) (PDMS) elastomers are widely used in biological laboratories to produce prototype micro-bioreactors. The need was identified for a simple modification of the PDMS surface to prevent protein adsorption and cell attachment in certain areas and to increase the level of cell attachment where desirable. A study has been undertaken into the effect on protein adsorption and cell attachment of adsorbed surfactants and sodium hydroxide (NaOH) modification of the surface. The proteins are adsorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 15 publications
3
78
0
Order By: Relevance
“…Overall, with an experimental condition of 32 h, minimum serum protein adsorption and fibroblast adhesion were achieved using 3% Pluronic F68, which was able to reduce serum protein adsorption and fibroblast adhesion ( Fig. 1) (replotted from our previous study [32] with a further statistic analysis) by 84.6 and 94.6%, respectively over the untreated PDMS surface. However, the long-term capability of Pluronic surfactant to deter cell adsorption is unknown.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Overall, with an experimental condition of 32 h, minimum serum protein adsorption and fibroblast adhesion were achieved using 3% Pluronic F68, which was able to reduce serum protein adsorption and fibroblast adhesion ( Fig. 1) (replotted from our previous study [32] with a further statistic analysis) by 84.6 and 94.6%, respectively over the untreated PDMS surface. However, the long-term capability of Pluronic surfactant to deter cell adsorption is unknown.…”
mentioning
confidence: 95%
“…Therefore the evaluation of the effectiveness of these surfactants to inhibit protein adsorption from serum-supplemented culture medium and the subsequently induced cell adhesion is practically important. In our previous study, [32] the capabilities of Pluronic F127 and F68 and, Tween 20 surfactants, to prevent serum protein adsorption and fibroblast adhesion on PDMS surfaces were evaluated at various concentrations using X-ray photoelectron spectroscopy (XPS) and an MTT cell viability assay, respectively. Briefly, the results demonstrated that Pluronic surfactants (F127 and F68) were more effective than Tween 20 surfactant in both the capabilities and, within the conditions investigated, minimum protein adsorption and cell adhesion occurred at a concentration ranges slightly lower than the critical micelle concentration (CMC).…”
mentioning
confidence: 99%
“…Gas-phase processing methods include plasma oxidation (14)(15)(16), ultraviolet (UV) irradiation (17)(18) and chemical vapor deposition (CVD) (19). Wet chemical methods include layer-by-layer (LBL) deposition (20), solgel coatings (21), silanization (22), dynamic modification using surfactants (23) and protein adsorption. Finally, the combined gas-phase and wet chemical methods includes silanization and LBL methods on PDMS pretreated via methods such as plasma oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Other strategies not involving polymeric physisorption can be found in the literature. For instance, Boxshall and co-workers [44] have found another surface treatment of PDMS to reduce protein adsorption using surfactants.…”
Section: Physisorptionmentioning
confidence: 99%